Analysis Of The Impact Of Internet Technology Advancement Innovations On Its Use As One Of The Marketplace Platforms And Sales Levels While Using The Platform - Ika Wisudawaty; Mitha Evalista (International Journal of Economics, Business and Innovation Research, 2024)
Internet technology has brought great changes in various aspects of human life, including in the fields of business and economics. Online marketplace platforms act as intermediaries that provide additional infrastructure, rules, and services that can facilitate and improve the quality of transactions, as well as address market issues such as access fees, information asymmetry, or trust. This article tries to analyze the impact of internet technology advancement innovations on the use of online marketplace platforms as a form of digital business, as well as the level of sales while using the platform. In this study, we analyze the impact of internet technology advancement innovations on the utilization of marketplace platforms and sales levels. The results of the study show that the use of marketplace platforms has provided a number of benefits for business actors, including increased market access, operational efficiency, increased visibility and brand awareness, as well as collaboration and networking opportunities.